Reposisi Etika Negara: Membedah Skandal Perpajakan Dan Jalan Reformasi Fiskal Indonesia - Intan Aulia; Zahwa Keyla Safira; Ghilma Novia Rizki; Yuliana Yuliana; Fanisa Juliana; Uli Artha Lestari (Prodi PGSD Unsultra, 2026)
Tax scandals in Indonesia over recent years indicate a serious ethical crisis in the state’s fiscal governance, which has significantly reduced public trust in tax institutions. Various practices such as aggressive tax avoidance by large corporations, leakage in tax administration systems, and alleged collusion between state officials and taxpayers demonstrate that taxation issues are not merely technical, but also deeply rooted in ethical dimensions of governance. This article aims to analyze the forms of state ethical crisis within tax scandals and to formulate the repositioning of state ethics in Indonesia’s fiscal reform agenda. The study employs a qualitative approach using a case study method and document analysis of secondary data sources, including government reports, fiscal policy publications, media coverage, and academic journals related to taxation. The findings reveal that weak bureaucratic integrity, low transparency in tax administration systems, and regulatory loopholes are the primary drivers of tax scandal occurrences. In addition, weak law enforcement further exacerbates public distrust in the fiscal system. Therefore, repositioning state ethics becomes an urgent necessity through strengthening institutional integrity, implementing digital tax systems, improving transparency, and enforcing non-discriminatory law enforcement. Fiscal reform in Indonesia should not only focus on technical and administrative improvements but must also be grounded in strong public ethics, transparency, and accountability to build a sustainable and trustworthy taxation system.